Examining Factors Affecting Employee Turnover Intention in Small and Mid-Sized Information Technology Organisations: Turnover Intention - K S, Sandhya (Ushus Journal of Business Management, 2024)
This abstract explores the pivotal success factors within the Indian Information Technology (IT) industry, focusing on human resources, strategic planning, and governmental policies. The rapid expansion of the Indian IT sector has led to a growth in the IT talent pool, significantly influencing the trajectory of IT organizations. The critical elements of talent attraction, management, and retention play a central role in shaping the future of these organizations. Talent management, a cornerstone organizational function, encompasses recruiting individuals for specific roles, fostering their growth, and empowering them to achieve organizational goals. Recognizing employees as valuable assets is essential, as their treatment fundamentally defines organizational success. Elevated employee engagement establishes positive emotional connections, fostering passionate contributors, innovative problem-solving teams, superior coordination, and enhanced employee well-being.